Real-World Assessment of All-Cause Hospital Readmissions among Pulmonary Embolism Patients Treated With Rivaroxaban Versus Apixaban - Veronica Ashton MPH; Guillaume Germain MSc; Julien Boudreau MA; Manasvi Sundar MPH; Sean D MacKnight MScPH; Shawn Murphy MD, PhD; Yichuan G. Hsieh PhD; François Laliberté MA (Clinical and Applied Thrombosis/Hemostasis)
Background Although hospital readmission after pulmonary embolism (PE) is common, there is limited evidence on the comparative risk of readmission between rivaroxaban and apixaban. This study compared the real-world risk of all-cause hospital readmission among patients with PE treated with rivaroxaban or apixaban. Methods This retrospective study used data from Mass General Brigham's Research Patient Data Registry (01/2013-05/2023) to identify adult patients newly initiated on rivaroxaban or apixaban during a PE-related hospitalization (discharge = index). Patients with venous thromboembolism in the 3 months prior to the index PE hospitalization were excluded. All-cause hospital readmissions at 30, 60, and 90 days post-index were assessed using Kaplan-Meier analysis and were compared between cohorts using hazard ratios (HRs), 95% confidence intervals (CIs), and p-values from Cox proportional hazards regression models. Inverse probability of treatment weighting was used to adjust for baseline confounding. Results In total, 686 rivaroxaban (mean age: 59.5; female: 50.1; Quan-Charlson comorbidity index: 1.51) and 2207 apixaban (mean age: 60.6; female: 50.8; Quan-CCI: 1.58) initiators were included. Rivaroxaban was associated with a 26% lower risk of all-cause hospital readmission at 30 days post-index (12.3% vs 16.5%; HR [95% CI]: 0.74 [0.58, 0.94]; P  = .012). Risk of hospital readmission was also significantly lower at 60 days (17.0% vs 22.3%; HR [95% CI]: 0.74 [0.61, 0.91]; P  = .004) and 90 days post-index (21.6% vs 25.6%; HR [95% CI]: 0.81 [0.68, 0.98]; P  = .029). Conclusions Rivaroxaban was associated with significantly lower risk of all-cause hospital readmission within 90 days post-discharge from PE-related hospitalization than apixaban.